Hermit crabs from Brazil: Family Paguridae (Crustacea: Decapoda: Paguroidea), except Pagurus - Nucci, Paulo Ricardo; de Melo, Gustavo Augusto Schmidt (Zootaxa, 2011)
In a previous paper we presented the species of the genus Pagurus recorded from Brazil. Here, we present the other 12 genera of the family Paguridae that occur in Brazil, with diagnoses, synonymies, illustrations and keys to species. These 12 genera include 16 species, some of which were found recently and only in deeper waters. This suggests the need for further studies in areas that have been little studied in Brazil.